High‐Performance Quasi‐2D Perovskite/Single‐Walled Carbon Nanotube Phototransistors for Low‐Cost and Sensitive Broadband Photodetection. Issue 2 (16th November 2020) - Liu, Chun-Ki; Loi, Hok-Leung; Cao, Jiupeng; Tang, Guanqi; Liu, Fang; Huang, Qi; Liang, Xuelei; Yan, Feng
Abstract : Quasi‐2D Ruddlesden–Popper perovskites (RPPs) have emerged as promising functional materials for optoelectronics due to the highly tunable optoelectronic properties and have been considered as alternative candidates for semiconductors in photodetectors. However, RPPs normally show low carrier mobilities, which is unfavorable for the performance of photodetectors. Herein, a solution‐processed hybrid phototransistor based on RPP/single‐walled carbon nanotube (SWCNT) heterostructure is reported. A vertical composition gradient is formed upon RPP film preparation, which leads to a gradient type‐II heterojunction in the film. More importantly, the high carrier mobility of SWCNTs can result in ultrahigh responsivity and detectivity of 2 × 10 6  A W −1 and 7 × 10 14  Jones, respectively. In addition, high on/off ratio of ≈10 3 can be achieved in the phototransistors. Herein, the high potential of RPP/SWCNT hybrid phototransistors as next‐generation photodetectors with superior sensitivity is demonstrated. Abstract : A solution‐processed high‐performance hybrid phototransistor based on Ruddlesden–Popper perovskite (RPP)/single‐walled carbon nanotube (SWCNT) heterostructure is developed. Responsivity and detectivity of up to 2 × 10 6  A W −1 and 7 × 10 14  Jones can be achieved. Such impressive performance is due to the efficient carrier separation in the device, improved perovskite film quality and excellent transport properties of SWCNTs.